Birds and hard ticks (Acari: Ixodidae), with discussions about hypotheses on tick evolution (FAVE Sección Ciencias Veterinarias, 2017)
The relationship between birds (Aves) and hard ticks (Ixodidae) was analyzed for the 386 of 725 tick extant species whose larva, nymph and adults are known as well as their natural hosts. A total of 136 (54 Prostriata= Ixodes, 82 Metastriata= all other genera) are frequently found on Aves, but only 32 species (1 associated with Palaeognathae, 31 with Neognathae) have all parasitic stages feeding on birds: 25 Ixodes (19% of the species analyzed for this genus), 6 Haemaphysalis (7%) and 1 species of Amblyomma (2%). The species of Amblyomma feeds on marine birds (MB), the six Haemaphysalis are parasites of non-marine birds (NMB), and 14 of the 25 Ixodes feed on NMB, one feeds on NMB and MB, and ten on MB. The Australasian Ixodes + I. uriae clade probably originated at an uncertain time from the late Triassic to the early Cretaceous. It is speculated that Prostriata first hosts were Gondwanan theropod dinosaurs in an undetermined place before Pangaea break up; alternatively, if ancestral monotromes were involved in its evolution an Australasian origin of Prostriata seems plausible. As for Prostriata the Motherland of Ixodida is probably Gondwana.
Keywords: Aves; Ixodidae; Prostriata; Metastriata; evolution